The Effect of Chitosan in Suppressing the Development of the Sheath Blight Disease (Rhizoctonia solani Khun) on Rice (Oryza sativa L.) - Okke Rosmala Dewi; Muhamad Tandi M; Umi kulsum (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
Rhizoctonia solani is a fungal disease in rice plants that can cause damage to rice plants and reduce yield by 50% -80%. This disease is difficult to control because it can survive in the soil for 2 years and spread easily. Efforts to control R. solani by using synthetic pesticides can couse negative impacts such as resistance, resurgence in plant pests. Therefore, alternative controls that are environmentally friendly and effective on target are needed. One of them is controling by using chitosan (extrct of shrimp shell waste) as a producer of antibiotics and amine (-NH2) functional groups. The purpose of this study is to obtain an effective concentration that can control and inhibit the development of Rhizoctonia solani both in vitro and in the field. The study was conducted in July 2018 - March 2019 at the Central Plant Pest Organisms Jatisari. The experiment used was a Randomized Block Design method with 8 treatments of chitosan concentration and 3 replications with a total of 24 plots. The results showed that powder of chitosan was able to supprese the growth of R solani colony and reduce diseases intensity of R. solani. The best in vitro treatment to suprpress growth of R. solani that was the concentration of 1.5%. This treatment inhibit mycelium growth by 77.37 % and sclerotia by 81.13 % while in the field experiment, it can inhibit the intensity of R. solani attacks by 9.67%.